Effectiveness of Critical Thinking Indicator-Based Module in Empowering Studentâs Learning Outcome in Respiratory System Study Material - Khasanah, A. N.; Widoretno, S.; Sajidan, S. (Jurnal Pendidikan IPA Indonesia, 2017)
Research and development are aiming to develop critical thinking skills-based modules on the respiration system materials to empower the learning outcomes; verify the effectiveness of critical thinking skills-based modules with teaching materials in schools based on student learning outcomes. Research and development method are using Borg & Gall development procedure with nine phases. Data analysis that used for the research and development are qualitative and quantitative descriptive. Research and development results show that critical thinking skills-based modules on the respiration system materials were developed according to the indicators of critical thinking skills and knowledge dimension that visualised on the objectives, materials, activities and evaluation questions which are developed to empower the learning outcomes. The result of module effectiveness test, showed by Anacova test result are FCount = 180,4 on factual, conceptual, procedural learning outcomes which are visualised in the form of multiple choice questions and FCount = 40.2 metacognitive learning results are visualised in the form of essays.